The relationship between smoking frequency and life satisfaction: Mediator of self-rated health (SRH) - Kang, Weixi (Frontiers in Psychiatry, 2022)
Background It is well-established that smoking is associated with life satisfaction. However, much less is known about how smoking frequency is related to life satisfaction and if self-rated health (SRH) mediates such a relationship. This is important to understand because life satisfaction is related to a lot of outcomes such as morbidity and mortality. The aim of the current study is to test whether smoking frequency relates to life satisfaction via SRH pathway. Method Data were extracted from Wave 7, Understanding Society: the UK Household Longitudinal Study (UKHLS). After removing non-smokers and participants with missing variables of interest, 5, 519 smokers out of 39, 293 participants remained for further analysis. Correlation coefficients were calculated between smoking frequency, SRH, and life satisfaction. Mediation analysis was performed by taking smoking frequency as the predictor, SRH as the mediator, life satisfaction as the outcome variable, and demographics as covariates using the mediation toolbox on MATLAB 2018a with 10000 bootstrap sample significance testing (https://github.com/canlab/MediationToolbox). Results The current study found a negative correlation between smoking frequency and life satisfaction (r=-0.09, 95% C.I [-0.12, -0.06], p<0.001) and between smoking frequency and SRH (r=-0.17, 95% C.I [-0.14, -0.19], p<0.001), and a positive correlation between SRH and life satisfaction (r=0.44, 95% C.I [0.41, 0.46], p<0.001). Results from the mediation analysis revealed that there is a significant effect of Path a (i.e., smoking frequency to SRH; β=-0.02, p<0.001, 95% C.I. [-0.02, -0.02]), Path b (SRH to life satisfaction; β=0.68, p<0.001, 95% C.I. [0.66, 0.69]), Path c' (direct effect; β=-0.01, p<0.01, 95% C.I. [0.66, 0.69]), Path c (total effect; β=-0.02, p<0.001, 95% C.I. [-0.02, -0.02]), and Path a*b (mediation effect; β=-0.01, p<0.001, 95% C.I. [-0.01, -0.014]). Conclusion SRH partially mediates the negative relationship between smoking frequency and life satisfaction. Findings from the current study may imply that antismoking campaigns and pamphlets are needed to counter the promotion of smoking by the tobacco industry. Moreover, interventions are needed for current smokers to reduce their smoking frequency to improve their life satisfaction, which can promote life satisfaction and positive outcomes associated with better life satisfaction.